(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
General Background: Imitative words in the Uzbek language have traditionally been classified into two categories based on internal structure: imitative words for sound and for action-state. Specific Background: Prior linguistic analyses have mainly focused on these two divisions, overlooking other potential imitative forms. Knowledge Gap: Existing classifications do not account for imitation directed at linguistic units themselves, such as lexemes, phrases, or stylistic expressions, limiting a full understanding of their structural diversity. Aim: This study aims to expand the internal structural classification of imitative words by proposing a third group: imitative words for language units. Results: Through analysis of literary examples, particularly the works of Tog‘ay Murod, it was found that many words—such as non-pon, kasal-pasal, and qishloq-pishloq—demonstrate imitation of linguistic units by phonetic alteration and repetition, especially involving the consonants (p), (m), and (s). These imitative forms serve semantic functions like generalization, emphasis, or abstraction. Novelty: The research introduces a previously unrecognized class of imitative words that replicate language units rather than sound or state, and argues for their recognition as a distinct subcategory within Uzbek linguistic studies. Implications: Acknowledging imitative words for language units enables a deeper understanding of stylistic devices in Uzbek and provides a refined framework for studying word formation, semantics, and colloquial usage patterns in Turkic languages.